2020
DOI: 10.1111/nan.12655
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix remodelling is associated with muscle force increase in overloaded mouse plantaris muscle

Abstract: Overload induced muscle dystrophy causes extracellular matrix remodelling as seen by upregulation of genes associated with the gene ontology (GO)‐terms “collagen metabolism”, “metalloproteinases”, and “inflammatory response”. These changes go in parallel with a more than twofold increase in muscle force and muscle weight.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
(96 reference statements)
2
10
0
Order By: Relevance
“…It could be speculated that enhanced postexercise extracellular matrix remodeling may be an important adaptation to facilitate the gains in muscle mass and/or maximal strength that occur following more prolonged resistance-type exercise training. In support, recent work demonstrates that enhanced extracellular matrix remodeling is associated with increases in muscle mass and strength in overloaded rodent plantaris muscle (Stantzou et al, 2020). Further exploration is required to determine whether the association between enhanced extracellular matrix remodeling and increases in muscle mass and strength following resistance-type exercise training in humans is causal.…”
Section: Discussionmentioning
confidence: 91%
“…It could be speculated that enhanced postexercise extracellular matrix remodeling may be an important adaptation to facilitate the gains in muscle mass and/or maximal strength that occur following more prolonged resistance-type exercise training. In support, recent work demonstrates that enhanced extracellular matrix remodeling is associated with increases in muscle mass and strength in overloaded rodent plantaris muscle (Stantzou et al, 2020). Further exploration is required to determine whether the association between enhanced extracellular matrix remodeling and increases in muscle mass and strength following resistance-type exercise training in humans is causal.…”
Section: Discussionmentioning
confidence: 91%
“…In support, findings from recent work demonstrated that enhanced ECM remodeling is associated with increases in muscle mass and strength in overloaded rodent plantaris muscle. 16 More exploration is required to determine whether the association between enhanced ECM remodeling and increases in muscle mass and strength following resistance-type exercise training in humans is both real and causal.…”
Section: The Impact Of Physical Activity On Collagen Remodelingmentioning
confidence: 99%
“…The ECM is an important source of growth factors, providing the attachment and controlled release of many growth factors and signal molecules, thereby aiding cell-to-cell signaling ( Birch, 2018 ). Transcriptome studies showed that in the rat model of overload, the expression abundance of the MSTN gene decreased, a large number of extracellular matrix-related proteins increased, and skeletal muscle increased ( Mendias et al, 2017 ; Stantzou et al, 2021 ). Biological scaffolds composed of ECM have been shown to facilitate the functional reconstruction of several tissue types including the esophagus ( Badylak et al, 2005 ; Desai et al, 2006 ), heart and vascular structures ( Badylak et al, 2006 ; Quarti et al, 2011 ), lower urinary tract ( Reddy et al, 2000 ; Boruch et al, 2010 ), and musculoskeletal tissues ( Smith et al, 2004 ; Franklin et al, 2008 ; Turner et al, 2010 ; Valentin et al, 2010 ; Zhao and Bass, 2018 ), among others.…”
Section: Discussionmentioning
confidence: 99%